Peningkatan Kompetensi Pedagogik Guru Berbasis Informations and Communication Technologies: Increasing Teacher Pedagogical Competence Based on Information and Communication Technologies - Kusnadi, Asep (STAI Publisistik Thawalib Jakarta, 2024)
Research aimed at explaining the enhancement of teachers' pedagogical competence through Information and Communication Technologies using qualitative methods with a literature review approach. Data was gathered through relevant literature to grasp the concepts, theories, and information and Communication Technologies practices in education. Data processing techniques involved data reduction, presentation, and triangulation of sources to validate research findings. The research results indicate that enhancing pedagogical competence through Information and Communication is crucial for optimizing learning. Teachers need to master learning management that considers individual student needs, designs and implements effective teaching methods and systematically evaluates learning outcomes. On the other hand, information and Communication Technologies encompass technologies such as computers, the internet, and audiovisual media that support communication and information distribution. Strategies to achieve these goals include teacher training to understand student characteristics in the technology era, developing technology-integrated curricula, and providing educational infrastructure that supports efficient access and communication.